CONTRIBUTION OF LEADERSHIP STYLE, MOTIVATION, ORGANIZATIONAL CULTURE AND SOCIAL COMPETENCE ON TEACHER PERFORMANCE AT SMP BATIK SURAKARTA - Wakhidah, Umi; Aryati, Ida; Sarsono, Sarsono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this research know that leadership style, motivation, organizational culture and social competence have a simultaneous effect on teacher performance. Motivation has an effect on teacher performance. Satisfaction has an effect on teacher performance and knowing compensation has an effect on teacher performance at SMP Batik Surakarta. The research method is in the form of survey research using quantitative with a sample of about 48 teachers. The data collection method used a questionnaire saturated sampling technique. Primary data is used as a source of primary data. Processing the data using the SPSS program using multiple regression equation analysis tools, t test, F test and coefficient of determination test (R2). The results the analysis variables: Leadership Style, Motivation,Organizational Culture and Social Competence have a simultaneous effect on the performance Surakarta Batik Junior High School teacher and Leadership_Style, Motivation, Organizational Culture and Social Competence have a significant effect on the performance of the SMP Batik Surakarta teacherpartially/individually. The results of the observations show that simultaneously the independent variables which include Leadership Style, Motivation, Organizational Culture and Social Competence have a relationship with teacher performance